A climatological validation of urban air temperature and electricity demand simulated by a regional climate model coupled with an urban canopy model and a building energy model in an Asian megacity. (4th April 2017) - Takane, Yuya; Kikegawa, Yukihiro; Hara, Masayuki; Ihara, Tomohiko; Ohashi, Yukitaka; Adachi, Sachiho A.; Kondo, Hiroaki; Yamaguchi, Kazuki; Kaneyasu, Naoki
ABSTRACT: In this study, we validated urban air temperature and electricity demand by a year‐round numerical simulation using a regional climate model coupled with an urban canopy model and a building energy model (RCM‐UCM+BEM) in the Asian megacity, Osaka, which is the largest metropolis in Japan after Tokyo. The control simulation (CTRL), which was based on the use of central air‐conditioning (AC) systems, reproduced the surface air temperatures observed in Osaka City in the summer cooling and interim seasons, but underestimated midnight to morning temperatures by over 2 °C in the winter heating season. In addition, the CTRL significantly overestimated the electricity demand in Osaka City in both the cooling and heating seasons, when the AC load was increased. These errors were likely due to the overestimation of AC use in the CTRL model because, in Japan, central AC systems are not used in business and residential areas, where individual AC units are mainly used. To prevent this overestimation, we introduced three new parameters to consider the use of partial AC systems in the model. The results of the new numerical experiment remarkably reduced the underestimation of temperature and the overestimation of electricity demand. This suggests that the RCM‐UCM+BEM modified by this study is effective for not only reproducing the current status of seasonal urban air temperature and electricity demand in Osaka, but also for projecting the future situation in other mega cities.